A burning in my bones eaudiobook The authorized biography of eugene h. peterson, translator of the message. - Collier, Winn (Random House Audio, 2021)
This essential authorized biography of Eugene Peterson offers unique insights into the experiences and spiritual convictions of the iconic American pastor and beloved translator of The Message. “In the time of a generation-wide breakdown in trust with leaders in every sphere of society, Eugene’s quiet life of deep integrity and gospel purpose is a bright light against a dark backdrop.”—John Mark Comer, author of The Ruthless Elimination of Hurry “This hunger for something radical—something so true that it burned in his bones—was a constant in Eugene’s life. His longing for God ignited a ferocity in his soul.”   Encounter the multifaceted life of one of the most influential and creative pastors of the past half century with unforgettable stories of Eugene’s lifelong devotion to his craft and love of language, the influences and experiences that shaped his unquenchable faith, the inspiration for his decision to translate The Message, and his success and struggles as a pastor, husband, and father.   Author Winn Collier was given exclusive access to Eugene and his materials for the production of this landmark work. Drawing from his friendship and expansive view of Peterson’s life, Collier offers an intimate, beautiful, and earthy look into a remarkable life.   For Eugene, the gifts of life were inexhaustible: the glint of fading light over the lake; a kiss from his wife, Jan; a good joke; a bowl of butter pecan ice cream. As you enter into his story, you’ll find yourself doing the same—noticing how the most ordinary things shimmer with a new and unexpected beauty.